Хөрвүүлэх програмд зөв бичих зүйн дүрмийг таниулсан нь - Э.Мөнх-Учрал (Acta Mongolica, 2007)
In this paper we consider about Mongolian orthographies in the employ oftranslation software. The translation software between Cyrillic and Mongol script which has been developed by scientists at the National University of Mongolia and the University of Science and Technology has a number of functions: converting a text file written in Cyrillic into Mongol script and vice versa; Cyrillic spelling check; and Mongol script spelling check. The major part of the translation software is a database, which contains more than 60,000 words according to the orthography of Mongol script and Cyrillic, and a parsing algorithm. The paper has the following parts: 1. The concepts which are used to word classification associated with orthography are: Parts of Speech Orthographical Classification - Word vowel These concepts are the medium between word stem and its inflected form. A much more confident way of translation is via these concepts. Its combination can give perfect information about the word. The combination is represented in a code which consists of 3 parts, for example, 1.1.1. The first number indicates parts ofspeech; the second is for main orthographical classification; the third is for word vowel. 2. Cyrillic features and employs it to the software, and prospective preconception: Following the Cyrillic orthography, the nouns in the database are classified into 32 main groups, and there are 16 main groups of verbs. Most groups have 4 versions because of vowels, for example, the ablative case: ‘aac, ooc, oec, ooc’ Cyrillic prefers phonetic principle in its orthography which is not suitable for the agglutinative Mongolian language. In 2006, an improved and more sophisticated Cyrillic orthography was developed by Mongolian philologists. This orthography prefers morphological principle, Mongolian phonetic distribution, vowel harmony, consonant harmony and it does not lead to break structures of word stem and suffixes.